2014
DOI: 10.1111/micc.12126
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Protects Rat Microvascular Endothelial Cells against Microwave Radiation‐induced Injury by Attenuating Endoplasmic Reticulum Stress

Abstract: Exogenous CRT attenuates MR-induced ER stress-related apoptosis by suppressing CHOP-mediated apoptotic signaling pathways in MMECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Calreticulin, a major Ca 2+ binding ER chaperone plays an important role in the adequate folding of newly synthesized proteins [73]. Therefore, fluctuations or alterations in Ca 2+ level in the ER might impact folding capacity and initiate the components of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Calreticulin, a major Ca 2+ binding ER chaperone plays an important role in the adequate folding of newly synthesized proteins [73]. Therefore, fluctuations or alterations in Ca 2+ level in the ER might impact folding capacity and initiate the components of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Their data showed that exposure to the highest power level (12 W) resulted in a decrease in HSP90 levels in the thymus, while the expression of HSP70 remained relatively unchanged in both groups, consistent with the results of this experiment. Currently, research on microwave irradiation and CRT protein is mainly focused on investigating the protective role of CRT against microvascular endothelial cell damage after irradiation by reducing endoplasmic reticulum stress [24]. In our study, we primarily investigated the expression of CRT protein in rat spleens after microwave irradiation and explored its potential as an indicator of the immune status of the rat spleen after irradiation.…”
Section: Discussionmentioning
confidence: 99%